Global Geopolitical Uncertainty and Islamic Capital Market Research in Indonesia: A Systematic Literature Review: Ketidakpastian Geopolitik Global dan Implikasinya Terhadap Pasar Modal Syariah Indonesia - Anselah, Suman; Elfinasari; Hamsah B Idris; Mamta Culkari (Robust: Research of Business and Economics Studies, 2026)
Global geopolitical uncertainty has become an important factor affecting the stability of financial markets, including Islamic capital markets. Although studies on geopolitical risk have grown rapidly, systematic reviews on its implications for the Indonesian Islamic capital market remain limited. Therefore, this study aims to systematically map the development of research on global geopolitical uncertainty and its implications for the Indonesian Islamic capital market. This study employs a Systematic Literature Review (SLR) based on the PRISMA guidelines. Literature was collected from the Dimensions database for the 2015–2025 period. Of the 499 articles identified, 35 met the inclusion criteria and were analyzed using VOSviewer. The findings show that all eligible studies were published during 2022–2025, with dominant themes including geopolitical risk, uncertainty, spillover, connectedness, Islamic stock, and sukuk. This study contributes by providing a comprehensive synthesis of the literature, identifying major research themes and gaps, and offering a foundation for future studies on the resilience of the Indonesian Islamic capital market under global geopolitical uncertainty.